2023
DOI: 10.1021/acs.nanolett.2c04425
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Transport Properties Driven by Unique Bonding Configuration in γ-GeSe

Abstract: Group IV monochalcogenides have recently shown great potential for their thermoelectric, ferroelectric, and other intriguing properties. The electrical properties of group IV monochalcogenides exhibit a strong dependence on the chalcogen type. For example, GeTe exhibits high doping concentration, whereas S/Se-based chalcogenides are semiconductors with sizable bandgaps. Here, we investigate the electrical and thermoelectric properties of γ-GeSe, a recently identified polymorph of GeSe. γ-GeSe exhibits high ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…For single-layer GeS, the electron and hole mobilities were predicted to reach 2750 and 220 cm 2 V –1 s –1 , respectively . α-GeSe is isostructural and isoelectronic to BP and has strong in-plane anisotropic properties. , A carrier mobility of 128.6 cm 2 V –1 s –1 was found for α-GeSe along with an room-temperature resistivity of 0.82 Ω cm . The resistivity increases dramatically with decreasing temperature below ∼100 K, but decreases slightly with decreasing temperatures above ∼200 K due to the high mobility of carriers .…”
Section: Ge Monochalcogenidesmentioning
confidence: 98%
See 2 more Smart Citations
“…For single-layer GeS, the electron and hole mobilities were predicted to reach 2750 and 220 cm 2 V –1 s –1 , respectively . α-GeSe is isostructural and isoelectronic to BP and has strong in-plane anisotropic properties. , A carrier mobility of 128.6 cm 2 V –1 s –1 was found for α-GeSe along with an room-temperature resistivity of 0.82 Ω cm . The resistivity increases dramatically with decreasing temperature below ∼100 K, but decreases slightly with decreasing temperatures above ∼200 K due to the high mobility of carriers .…”
Section: Ge Monochalcogenidesmentioning
confidence: 98%
“…Band diagrams for the single layers of GeS and α-GeSe are depicted in Figure a,b, respectively. Bulk GeS remains an indirect semiconductor with an established band gap of 1.56 eV, whereas reported direct and indirect band gaps of bulk α-GeSe range from 0.8–1.54 eV at room temperature. ,,, As shown in Figure c, γ-GeSe is an indirect semiconductor in the single layer limit with a calculated energy gap in the 0.99–2.96 eV range. Bulk γ-GeSe shows semimetallic properties owing to its high p-doping level and very small indirect band gap at or below 0.36 eV. , …”
Section: Ge Monochalcogenidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of fundamental research, exfoliation of 2D materials into mono- or few-layers preserves their characteristics and leads to additional properties due to quantum confinement effects. Furthermore, most of the layered materials exhibit polymorphism and different stacking polytypes, making them promising materials for study. , …”
Section: Production and Fabrication Of 2d Materialsmentioning
confidence: 99%
“…For instance, Ge and Sn monosulfide compounds containing S and Se exhibit the characteristics of large bandgap semiconductors, while those containing Te possess smaller bandgaps and exhibit higher doping concentrations. , As analogs of BP, Eli Sutter et al reported the successful fabrication of a large (up to 20 μm) ultrathin sheets of GeY (Y = Se; S) using a vapor transport process. These sheets demonstrate thermal and chemical stability in ambient air and exhibit anisotropic properties, making 2D GeS nanosheets, suitable for electronic devices. Leveraging the intrinsic band gap difference between GeY and AsP, absorption band tuning is expected to be achieved through AsP–GeSe heterojunctions.…”
Section: Introductionmentioning
confidence: 99%